KECEMASAN PADA IBU POST PARTUM PRIMIPARA DENGAN GANGGUAN PROSES LAKTASI - Ike Mardiati Agustin; Septiyana Septiyana (Jurnal Ilmu Keperawatan Jiwa, 2018)
ANXIETY IN  PRIMIPHARA POSTPARTUM MOTHERS WITH LACTATION TROUBLE ON  MATERNITY WARD ABSTRACTLabor or delivery is a normal physiological condition happens in life, especially to women. Changes in the role and process of newborn-baby care will lead to psychological problems. Anxiety is one of psychological problems that happens to primiphara mothers. Anxiety will affect the process of lactation (breastfeeding) for some primiphara mothers with psychological problems. This study is to provide an overview of a case study of nursing care for primiphara postpartum mothers who have problem with breastfeeding because of anxiety. This scientific paper is an analytical descriptive with a case study approach. The study was conducted on two primiphara mothers with anxiety in their breastfeeding. Data were obtained through interview, observation, and documentation. After having nursing care, there was a decrease in anxiety (patient 1: from 44.6% to be 30.3%, patient 2: from 32.1% to be 19.6 %). Besides, there is a difference in the increase of affective ability, with the highest increase patient 2 (60%) while patient 1 (40%). It is advisable for nurses to provide nursing care for primiphara postpartum mother with breastfeeding problem caused by anxiety. Keywords: Labor, primiphara, anxiety, lactation.